In-Season Repeated-Sprint Training in Hypoxia in International Field Hockey Players - James, Carl; Girard, Olivier (Frontiers in Sports and Active Living, 2020)
Repeated sprint training in hypoxia (RSH) studies conducted ‘in-season’ are scarce. This study investigated the effect of discontinuous, running-based RSH, on repeated sprint treadmill performance in hypoxia in a team sport cohort, prior to international competition. Over a 6-wk ‘in-season’ period, eleven elite male players (Malaysia national team) completed eight multi-set RSH sessions on a non-motorised treadmill in a normobaric hypoxic chamber (FiO2=13.8%). Three testing sessions (Sessions 1, 5 and 8), involved three sets of 5×8-s sprints, with 52-s recovery between sprints and 4-5 min between sets. Training sessions (Sessions 2, 3, 4, 6 and 7) consisted of 4-5 sets of 4-5×8-s sprints. During testing sessions, maximum sprinting speed was recorded for each sprint with values averaged for each set. For each set, a peak speed and fatigue index were calculated. Data were compared using two-way repeated measures ANOVA (sessions × sets). Average speed per set increased between testing sessions (p=0.001, ηp2=0.49), with higher values in Session 8 (25.1±0.9 km.h-1, +4±3%, p=0.005), but not Session 5 (24.8±1.0 km.h-1, +3±3%, p=0.405), versus Session 1 (24.2±1.5 km.h-1). Peak sprinting speed in each set also increased across testing sessions (p=0.008, ηp2=0.382), with Session 8 (26.5±1.1 km.h-1) higher than Session 5 (25.8±1.0 km.h-1, +1±4%, p=0.06) and Session 1 (25.7±1.5 km.h-1, +4±4%, p=0.034). Fatigue index differed between sessions (p=0.04, ηp2=0.331, Session 1; -6.8±4.8%, Session 5; -3.8±2%, Session 8; -5.3±2.6%). In international field hockey players, a 6-wk in-season RSH programme improved average and peak, repeated treadmill sprint speeds following eight, but not five sessions.